Microstructure and creep behavior of a new developed nickel‐base single‐crystal superalloy: Gefüge und Kriechverhalten einer neuentwickelten Nickelbasis‐Einkristall‐Superlegierung. Issue 10 (1st October 2018) - Xu, W.; Zhao, Y.; Sun, S.; Liang, X.; Tao, R.; Ma, D.
Abstract: A new developed nickel‐base superalloy is employed to prepare single‐crystal castings. The as‐cast and heat‐treated microstructure, the creep behavior in 900 °C/ 500 MPa and 1100 °C / 140 MPa are investigated. The dendrites are well developed in the as‐cast microstructure. Segregation and γ′ precipitation morphology difference exist between dendrite core and γ/γ′ eutectic pool. After heat treatment the segregation is significantly decreased and the γ′ precipitations of all regions become much more uniform and cubic. Creep curves in varied conditions both present three stages, while the specimen in 1100 °C exhibits lower creep rate and longer life span. The fracture analysis shows that fracture style changes from mixed fracture to ductile when the temperature increases from 900 °C to 1100 °C. Porosity is the crack resource to form the facet, which is observed in both specimens. The γ′ precipitations raft in both specimens, while the further development of γ′ rafting is found in that of 1100 °C / 140 MPa, as well as the surface recrystallization with coarser rafted γ/γ′ microstructure.